The resilience of rice under water stress will be driven by better roots: Evidence from root phenotyping, physiological, and yield experiments - Sadiah Shafi; Insha Shafi; Aaqif Zaffar; Sajad Majeed Zargar; Asif B. Shikari; Anuj Ranjan; P.V. Vara Prasad; Parvaze A. Sofi (Plant Stress, 2023)
Rice is the principal food grain crop of the world, grown on over 164 million hectares. Water is an important production constraint in food crops. Till recently, crop breeding efforts have mainly focused on the shoot, whereas most of the major drivers of the yield gap directly influence the root system, thereby implicating the plant's resource acquisition efficiency. Despite the substantial experimental evidence for the importance of root traits in drought tolerance, lesser efforts have been directed towards drought-adaptive root traits based on the selection index in rice. The above-ground components are easy to phenotype, and lesser efforts towards root traits stem mainly from the phenotyping bottlenecks of reliable recovery and evaluation of root traits. Moreover, greater phenotypic plasticity of root traits in response to changes in soil resource status, and lack of less costly screening techniques for roots is still a challenge, leading to comparatively lesser information about the potential role of roots in developing drought-resilient rice varieties. Root phenes are not as high in number as is the huge shopping list of above-ground traits and exploring the natural variation of root traits could assist rice improvement programs in developing varieties with desired root phenes for target environments. More importantly, elucidation of the relationship of root traits with the physiological and biochemical responses contributing to grain yield is also imperative. In this paper, we discuss the potential role of roots in determining the resilience of rice varieties for future farming systems based on evidence from root phenotyping, the relationship of root phenes with physiological efficiency and yield under water stress in rice.